SAT0014 ENDOTHELIAL PROGENITOR CELLS: ROLE IN ENDOTHELIAL DAMAGE OF INTERSTITIAL LUNG DISEASE ASSOCIATED TO RHEUMATOID ARTHRITIS. (2nd June 2020) - Pulito-Cueto, V.; Remuzgo-Martínez, S.; Genre, F.; Mora-Cuesta, V. M.; Iturbe Fernández, D.; Fernández-Rozas, S.; Lera-Gómez, L.; Alonso Lecue, P.; Rodriguez Carrio, J.; Atienza-Mateo, B.; Portilla, V.; Merino, D.; et al.
Abstract : Background: Interstitial lung disease (ILD) is one of the most significant comorbidities of rheumatoid arthritis (RA), increasing the mortality in these patients [1, 2]. Although the pathogenesis of ILD associated to RA (RA-ILD + ) remains poorly defined [1], it is known that vascular tissue plays a crucial role in lung physiology [3]. In this context, a population of cells termed endothelial progenitor cells (EPC) are involved in vasculogenesis and endothelial tissue repair [4]. Previous reports suggest the implication of EPC in different conditions such as RA and idiopathic pulmonary fibrosis (IPF), the most common and destructive ILD [5, 6]. Nevertheless, little is known about their specific role in RA-ILD + . Objectives: The purpose of this study was to shed light on the potential role of EPC in endothelial damage in RA-ILD +. Methods: Peripheral venous blood was collected from a total of 68 individuals (18 with RA-ILD +, 17 with RA-ILD -, 19 with IPF and 14 healthy controls). All subjects were recruited from the Rheumatology and Pneumology departments of Hospital Universitario Marqués de Valdecilla, Santander, Spain. Quantification of EPC was analyzed by the expression of surface antigens by flow cytometry. The combination of antibodies against the stem cell marker CD34, the immature progenitor marker CD133, the endothelial marker VEGF receptor 2 (CD309) and the common leukocyte antigen CD45 was used. EPC were considered as CD34 +, CD45 Low, CD309 + and CD133 + . All statistical analyses were performed using Prism software 5 (GraphPad). Results: EPC frequency was significantly increased in patients with RA-ILD +, RA-ILD - and IPF compared to controls (p=0.001, p=0.002, p< 0.0001, respectively). Nevertheless, patients with RA, both RA-ILD + and RA-ILD -, showed a lower frequency of EPC than those with IPF (p= 0.048, p= 0.006, respectively). Conclusion: Our results provide evidence for a potential role of EPC as a reparative compensatory mechanism related to endothelial damage in RA-ILD +, RA-ILD - and IPF patients. Interestingly, EPC frequency may help to establish a differential diagnostic between patients with IPF and those who have an underlying autoimmune disease (RA-ILD + ). References: [1] J Clin Med 2019; 8: 2038; [2] Arthritis Rheumatol 2015; 67: 28-38; [3] Nat Protoc 2015; 10: 1697-1708; [4] Science 1997; 275: 964-966; [5] Rheumatology (Oxford) 2012; 51: 1775-1784; [6] Angiogenesis 2013; 16: 147-157. Acknowledgments: Personal funds, VP-C: PREVAL18/01 (IDIVAL); SR-M: RD16/0012/0009 (ISCIII-ERDF); LL-G: PI18/00042 (ISCIII-ERDF); RL-M: Miguel Servet type I CP16/00033 (ISCIII-ESF). Disclosure of Interests: Verónica Pulito-Cueto: None declared, Sara Remuzgo-Martínez: None declared, Fernanda Genre: None declared, Victor Manuel Mora-Cuesta: None declared, David Iturbe Fernández: None declared, Sonia Fernández-Rozas: None declared, Leticia Lera-Gómez: None declared, Pilar Alonso Lecue: None declared, Javier Rodriguez Carrio: None declared, Belén Atienza-Mateo: None declared, Virginia Portilla: None declared, David Merino: None declared, Ricardo Blanco Grant/research support from: AbbVie, MSD, Roche, Consultant of: Abbvie, Eli Lilly, Pfizer, Roche, Bristol-Myers, Janssen, UCB Pharma and MSD, Speakers bureau: Abbvie, Eli Lilly, Pfizer, Roche, Bristol-Myers, Janssen, UCB Pharma. MSD, Alfonso Corrales Speakers bureau: Abbvie, Jose Manuel Cifrián-Martínez: None declared, Raquel López-Mejías: None declared, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD